Haematological spectrum and genotype-phenotype correlations in nine unrelated families with RUNX1 mutations from the French network on inherited platelet disorders. Issue 1 (December 2016) - Latger-Cannard, Veronique; Philippe, Christophe; Bouquet, Alexandre; Baccini, Veronique; Alessi, Marie-Christine; Ankri, Annick; Bauters, Anne; Bayart, Sophie; Cornillet-Lefebvre, Pascale; Daliphard, Sylvie; Mozziconacci, Marie-Joelle; Renneville, Aline; et al.
Abstract Background Less than 50 patients with FPD/AML (OMIM 601309) have been reported as of today and there may an underestimation. The purpose of this study was to describe the natural history, the haematological features and the genotype-phenotype correlations of this entity in order to, first, screen it better and earlier, before leukaemia occurrence and secondly to optimize appropriate monitoring and treatment, in particular when familial stem cell transplantation is considered. Methods We have investigated 41 carriers ofRUNX1 alteration belonging to nine unrelated French families with FPD/AML and two syndromic patients, registered in the French network on rare platelet disorders from 2005 to 2015. Results Five missense, one non-sense, three frameshift mutations and two large deletions involving several genes includingRUNX1 were evidenced. The history of familial leukaemia was suggestive of FPD/AML in seven pedigrees, whereas an autosomal dominant pattern of lifelong thrombocytopenia was the clinical presentation of two. Additional syndromic features characterized two large sporadic deletions. Bleeding tendency was mild and thrombocytopenia moderate (>50 x109 /L), with normal platelet volume. A functional platelet defect consistent with a δ-granule release defect was found in ten patients regardless of the type ofRUNX1 alteration. The incidence of haematological malignancies was higher when the mutatedRUNX1 allele was likely to cause a dominant negative effect (19/34) in comparison with loss of function alleles (3/9). A normal platelet count does not rule out the diagnosis of FPD/AML, since the platelet count was found normal for three mutated subjects, a feature that has a direct impact in the search for a related donor in case of allogeneic haematopoietic stem cell transplantation. Conclusions Platelet dysfunction suggestive of defective δ-granule release could be of values for the diagnosis of FPD/AML particularly when the clinical presentation is an autosomal dominant thrombocytopenia with normal platelet size in the absence of familial malignancies. The genotype-phenotype correlations might be helpful in genetic counselling and appropriate optimal therapeutic management.